1996
DOI: 10.1093/ndt/11.supp4.54
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular disease during HCV infection in renal transplantation

Abstract: In general nephrology, HCV infection has been associated with type I membranoproliferative glomerulonephritis (MPGN type I) associated with cryoglobulinaemia. In a cohort of 399 renal transplantation (RT) recipients, 117 of whom (29%) were HCV-positive, we selected all patients diagnosed as having membranous GN or type I MPGN by graft biopsy. The prevalence of MGN was 16/399 (4%) with three recurrences, and 13 de novo cases. Only 5/16 (31%) were HCV+, not different from the general RT population. Five patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 5 publications
2
27
1
Order By: Relevance
“…Altogether, our findings clearly show that a HCV-positive status is associated with an adverse outcome in renal transplant patients, as well as for renal survival after renal transplant. Our findings are in agreement with the findings of earlier similar studies [4, 5, 8, 13, 15, 29,31,32,33,34,35,36]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Altogether, our findings clearly show that a HCV-positive status is associated with an adverse outcome in renal transplant patients, as well as for renal survival after renal transplant. Our findings are in agreement with the findings of earlier similar studies [4, 5, 8, 13, 15, 29,31,32,33,34,35,36]. …”
Section: Discussionsupporting
confidence: 94%
“…In recent years, tremendous improvement has taken place in the short-term, 1-year survival of renal allograft due, mainly, to improved medical care and advanced therapeutic strategies. Apart from other risk factors, hepatitis virus infection is one of the important risk factors for the long-term deterioration of kidney function, reduced long-term graft and patient survival [2, 6, 8, 13, 29,31,32,33,34] and an increased incidence of graft rejection [5, 13, 15]. In contrast, several studies have shown no significant difference regarding graft and patient survival in HCV-positive and HCV-negative patients [10, 19, 35] and recommended renal transplant from/or to the HCV-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…De novo Ig-mediated MPGN develops uncommonly after transplantation and is associated with HCV in about one half of cases (34). In a French series, only 13 of 399 renal transplant recipients developed a de novo MPGN (35). Renal biopsy showed the typical MPGN pattern of mesangial hypercellularity accompanied by broadening of the peripheral capillary loops caused by reduplication of the GBM.…”
Section: Membranoproliferative Gnmentioning
confidence: 99%
“…Types II and III cryoglobulinemias are systemic vasculitides, and nearly half of the HCV-infected patients who have type II or III cryoglobulinemia develop renal complications, including membranoproliferative glomerulonephritis and membranous nephropathy (42). Therefore, in addition to its direct effects on the liver, HCV infection increases posttransplantation morbidity by enhancing the risk for de novo or recurrent HCV-associated glomerulopathies (43)(44)(45)(46)(47). Recurrence of HCV-associated kidney disease has the potential to adversely affect graft survival and has been linked to higher serum creatinine levels (44,48).…”
Section: Hcv-associated Posttransplantation Glomerulopathiesmentioning
confidence: 99%